Adaptación de una metodología ágil para desarrollo móvil, caso de estudio: módulo de seguimiento de actividades académicas - Cañizares Carvajal, Denise Alexandra (2022)
As the mobile application business expands and becomes profitable, optimal software development methodologies for such applications and environments have to be investigated to bring such development to success in an attractive and efficient manner. Mobile application developers face a range of new trends to create mobile software, so they have Mobile D, which is an agile methodology, exclusively for the development of mobile applications, allowing constant interaction between the work team and the client. , as well as responding quickly to changes that may occur during the development stage of the project, allowing the reduction of production times.